2006
DOI: 10.1089/jmf.2006.9.284
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Testosterone-Induced Hyperplasia of the Prostate of Sprague-Dawley Rats by Pumpkin Seed Oil

Abstract: The oil from the pumpkin (Cucurbita pepo) seed is claimed to be useful in the management of benign prostatic hyperplasia. This investigation seeks to examine the effect of pumpkin seed oil on testosterone-induced hyperplasia of the prostate of rats. Hyperplasia was induced by subcutaneous administration of testosterone (0.3 mg/100 g of body weight) for 20 days. Simultaneous oral administration of either pumpkin seed oil (2.0 and 4.0 mg/100 g of body weight) or corn oil (vehicle) was also given for 20 days. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
73
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(74 citation statements)
references
References 5 publications
0
73
0
1
Order By: Relevance
“…The enlarged prostate affects the urethra, and therefore BPH is associated with diminution in urinary function [48]. Management of this disease to include pumpk seeds suggested that the actions of pumpkin seed oil may be attributed to the content of phytosterols, which are known to interfere with the actions of dihydrotestosterone.…”
Section: Prostatic Hiperplasia (Bph) and Urinary Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enlarged prostate affects the urethra, and therefore BPH is associated with diminution in urinary function [48]. Management of this disease to include pumpk seeds suggested that the actions of pumpkin seed oil may be attributed to the content of phytosterols, which are known to interfere with the actions of dihydrotestosterone.…”
Section: Prostatic Hiperplasia (Bph) and Urinary Functionmentioning
confidence: 99%
“…Administration of pumpkin seeds oil (14 mg/kg) daily for 30 days inhibited testosterone-induced hyperplasia of the rat prostate involving a direct inhibition of growth of the prostate [48].…”
Section: Prostatic Hiperplasia (Bph) and Urinary Functionmentioning
confidence: 99%
“…The oral administration of high doses of pumpkin seeds and pumpkin seed oil reduced prostate weight in experimental animal models of prostate growth [3,8,9,10]. The injection of pumpkin seed oil caused reproducible effects on urodynamic parameters in rabbits [11].…”
Section: Introductionmentioning
confidence: 99%
“…Pumpkin seed oil has been implicated in providing many health benefits (66). The most critical health benefit attributed to pumpkin seed oil is preventing the growth and reducing the size of the prostate (67,68). There is also evidence that suggests pumpkin seed oil can retard the progression of hypertension (69) and mitigate hypercholesterolemia (70) and arthritis (71).…”
Section: Introductionmentioning
confidence: 99%